2015
DOI: 10.1111/gcb.13171
|View full text |Cite
|
Sign up to set email alerts
|

Humpback whale diets respond to variance in ocean climate and ecosystem conditions in the California Current

Abstract: Large, migratory predators are often cited as sentinel species for ecosystem processes and climate-related changes, but their utility as indicators is dependent upon an understanding of their response to environmental variability. Documentation of the links between climate variability, ecosystem change and predator dynamics is absent for most top predators. Identifying species that may be useful indicators and elucidating these mechanistic links provides insight into current ecological dynamics and may inform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 72 publications
2
137
0
Order By: Relevance
“…This assumes that the relative difference in prey δ 15 N values between foraging zones is consistent across years, which has been suggested in previous studies [58,91]. We evaluated this assumption by fitting a generalized linear model (GLM) of skin δ 15 N values as a function of time (Julian Date, or date of sample collection).…”
Section: Methodsmentioning
confidence: 98%
“…This assumes that the relative difference in prey δ 15 N values between foraging zones is consistent across years, which has been suggested in previous studies [58,91]. We evaluated this assumption by fitting a generalized linear model (GLM) of skin δ 15 N values as a function of time (Julian Date, or date of sample collection).…”
Section: Methodsmentioning
confidence: 98%
“…Fortunately, some marine mammals have exhibited substantial behavioral and prey selection flexibility . For example, humpback whales (Megaptera novaeangliae) remained abundant and were suspected to adapt foraging behavior to new prey species when climate conditions were unfavorable to common target prey species (Benson et al, 2002;Fleming et al, 2016). Failure to account for such flexibility could lead to unrealistically pessimistic projections.…”
Section: Marine Mammal Ecology and Climate Changementioning
confidence: 99%
“…northern anchovy, Pacific sardine and market squid), krill and juvenile groundfish (particularly rockfish) and other epipelagic micronekton (e.g. pelagic squid and mesopelagic fishes) as forage (Sydeman et al 2001, Weise & Harvey 2008, Thayer et al 2014, Glaser et al 2015, Fleming et al 2016, as illustrated by the high rankings of these groups in a meta-analysis of forage needs throughout the California Current ecosystem (CCE) (Ainley et al 2015, Szoboszlai et al 2015. In addition, there are 3 na tio nal marine sanctuaries located in the GoF/MB: Cor dell Bank, Gulf of the Farallones and Monterey Bay (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…When YOY rockfish are less available, breeding success tends to be lower, although the most severe declines occur during periods of unusual environmental conditions (such as El Niño events) that correspond with both very low YOY rockfish abundance and low productivity throughout the ecosystem more generally (Field et al 2010, Wells et al 2017. Similarly, humpback whales Megaptera novaeangliae may alter their foraging behavior between krill and northern anchovy as a function of climate-driven ocean conditions that determine which prey type is abundant, such that krill are preyed on more frequently in cool, high upwelling years and northern anchovy in years of lower productivity and warmer SST (Fleming et al 2016). Finally, Thayer et al (2014) showed that diets of adult Chinook salmon Oncorhynchus tshawytscha correspond to the forage assemblage quantified from the RREAS and that diet diversity had declined over time and was somewhat correlated with productivity.…”
Section: Trophic Considerations Of Epipelagic Fish Biodiversitymentioning
confidence: 99%